2014
DOI: 10.1136/jech-2014-204648
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among first-generation and second-generation immigrants in Sweden: association with labour market marginalisation and morbidity

Abstract: The risk of suicide was shown to be lower in the first generation and higher in the second generation compared with natives. The higher HR in the Nordic second generation was not explained by differences in sociodemographics, labour market marginalisation and morbidity. Further research is warranted to investigate factors underlying this excess risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
(25 reference statements)
3
32
0
Order By: Relevance
“…Lehti’s 2013 study in Finland found that children with two migrant parents had an increased likelihood of being diagnosed with autism [38], a direct opposite to the findings of the similar high-quality paper. Di Thiene’s 2015 study in Sweden concluded that migrants had a significantly lower risk of attempting suicide than the settled population [39]. Laubjerg’s study found that international adoptees have higher psychotic disorder rates than non-adoptees [40].…”
Section: Resultsmentioning
confidence: 99%
“…Lehti’s 2013 study in Finland found that children with two migrant parents had an increased likelihood of being diagnosed with autism [38], a direct opposite to the findings of the similar high-quality paper. Di Thiene’s 2015 study in Sweden concluded that migrants had a significantly lower risk of attempting suicide than the settled population [39]. Laubjerg’s study found that international adoptees have higher psychotic disorder rates than non-adoptees [40].…”
Section: Resultsmentioning
confidence: 99%
“…Another important task for future research is to investigate whether inequalities in health and mortality continue to exist among children of foreign-born individuals. In fact, some findings from the US have suggested that mortality risks increase in these children [24, 25], while evidence for changed suicide and gynaecological cancer mortality risks in second-generation immigrants in Sweden also exists [30, 31]. Based on the findings from this review there is also a clear need to stimulate more research within the field in the Nordic countries besides Sweden, and to compare mortality risks by country of birth between the Nordic countries using a comparative approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the inpatient care register, external codes are reported separately from the main and side diagnoses. We included events of undetermined intent in the final analysis in line with a number of previous papers [4, 10], to limit under-reporting and also to adjust for regional differences in ascertainment methods. A sensitivity analysis revealed the comparability of the estimates for the two outcome measures (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…While some 50 years ago, predominantly individuals with a European background formed the bulk of the workforce immigrants to Sweden, the last 30 years have seen increasing migration from refugees and non-European migrants with more diverse cultural and ethnic origins than the Swedish native population [7]. This diversity of migrant populations is reflected in differences with regard to access and use of healthcare [8], educational level [9], and prevalence of suicide attempt, [1] which all may impact on the risk of labour market marginalization [10]. …”
Section: Introductionmentioning
confidence: 99%